William and Mabel Meed standing on the bank of the Stewart River at Fraser Falls, Yukon Territory, 1902. - University of Washington Libraries. Special Collections Division
PH Coll 246.217 [Meed journal: "Fraser Falls, my wife and I together in 1902."] To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number